Prevalence, pattern and outcome of congenital malformations in a tertiary care centre in South India - Neelambari, Yazhini C.; Das, Prarthana; Sadagopan, Srinivasan; Uma, A. N. (International Journal of Contemporary Pediatrics, 2018)
Background: Congenital malformations are of major concern as they are cosmetically unacceptable, often associated with significant functional abnormalities and may sometimes even be life-threatening. This study was done to explore the prevalence of structural congenital malformation among hospital newborns, both live and stillborn in a tertiary care center in Southern India. Methods: This hospital-based prospective study involving all inborn neonates and still births was conducted for the period from January 2014 to December 2014. A total of 2276 newborn (2217 live births and 59 still births) were clinically examined for detection of gross congenital malformations and relevant investigations including karyotyping was done. Risk factors that had probable associations with birth defects were estimated by calculating the Odd’s Ratio. Statistical analysis was done using Chi-Square test. Results: The prevalence of congenital malformations was 12%. Major malformations accounted for 53.28% and minor malformations 46.71%. The commonest structural malformation involved cardiovascular system. 58% of neonates did not require life style medications whereas 21.17% required surgical intervention. 20.8% of the cases succumbed to death. Conclusions: Autopsy of stillborn babies should be done to evaluate the cause and incidence of malformations. High risk mothers should be identified in the antenatal period to detect malformations early and plan management accordingly.